Can Boracay Island accommodate more tourists? - Calanog, Lope A. (Ecosystems & Development Journal: a Journal on Tropical Forests and Natural Resources, 2012)
This study was undertaken to shed light on the reports that Boracay Island, particularly the 4-km White Beach destination, is overused and abused, and its carrying capacity (CARCAP) has been exceeded. Specifically, it determined the optimum number of tourists or visitors that can be accommodated in this particular area and the factors that have limited such carrying capacity. The study also established a simple demographic profile of the visitors, their preferences for tourism activities, and willingness to pay environmental protection.